Isovalent multi-component doping strategy for stabilizing cubic-Li7La3Zr2O12 with excellent Li mobility - Lee, Han Uk; Han, Seungmin; Lee, Dong Geon; Ko, Hyunseok; Lee, Juhyun; Im, Won Bin; Song, Taeseup; Choi, Junghyun; Cho, Sung Beom (Chemical Engineering Journal, 2023)
Stabilizing the cubic phase of Li7La3Zr2O12 (LLZO) through doping has been a challenging issue, as conventional aliovalent dopants often decrease Li ion mobility and induce unwanted phase transformations. In this study, a novel multi-component doping strategy is proposed that stabilizes the cubic phase of LLZO while maintaining high Li ion mobility. The practical isovalent ions and their combinations are screened using density-functional theory (DFT) calculations and ab-initio molecular dynamics (AIMD) simulations, identifying the most stable multi-component alloy configuration that can stabilize the robust cubic phase of LLZO. Our results demonstrate that the proposed Li7La3(Zr, Hf, Ce, Ru)2O12 composition has a stable cubic phase at low temperatures, which we validated through experimental synthesis. Our proposed doping strategy has the potential to advance the development of high-performance all-solid-state batteries.
Keywords: All-solid-state battery; Cubic phase; Doping strategies; Ion Mobility; Multi-component alloy; Multicomponents; Reduction sintering temperature; Reduction-sintering; Sintering temperatures; Solid-state electrolyte; All-solid-state battery; Li7La3Zr2O12; Multi-component alloy; Reduction sintering temperature; Solid-state electrolyte